Neural correlates of theory of mind in children and adults using CAToon: Introducing an open-source child-friendly neuroimaging task. (June 2021) - Borbás, Réka; Fehlbaum, Lynn V.; Rudin, Ursula; Stadler, Christina; Raschle, Nora M.
Abstract: Theory of Mind (ToM) or mentalizing is a basic social skill which is characterized by our ability of perspective-taking and the understanding of cognitive and emotional states of others. ToM development is essential to successfully navigate in various social contexts. The neural basis of mentalizing is well-studied in adults, however, less evidence exists in children. Potential reasons are methodological challenges, including a lack of age-appropriate fMRI paradigms. We introduce a novel child-friendly and open-source ToM fMRI task, for which accuracy and performance were evaluated behaviorally in 60 children ages three to nine (32♂). Furthermore, 27 healthy young adults (14♂; mean = 25.41 years) and 33 children ages seven to thirteen (17♂; mean = 9.06 years) completed the C ognitive and A ffective T heory of Mind Cartoon task (CAToon; www.jacobscenter.uzh.ch/en/research/developmental_neuroscience/downloads/catoon.html ) during a fMRI session. Behavioral results indicate that children of all ages can solve the CAToon task above chance level, though reliable performance is reached around five years. Neurally, activation increases were observed for adults and children in brain regions previously associated with mentalizing, including bilateral temporoparietal junction, temporal gyri, precuneus and medial prefrontal/orbitofrontal cortices. We conclude that CAToon is suitable for developmental neuroimaging studies within an fMRI environment starting around preschool and up.